The Causes of Poverty - Thurow, Lester C. (Quarterly Journal of Economics, 1967)
The poverty model, 40. — Farmers, 43. — Families with no one in the labor force, 44. — Education, 46. — Alaska and Hawaii, 47. — Full-time employment, 47. — Industrial structure, 48. — Nonwhites, 51. — Principal component analysis, 52. — Implications, 56.